Potential Pakraman Village in Achieving Bali Rabies Free - I Nyoman Jirna; I Gede Sudarmanto; Cok Dewi Widhya Hana Sundari; I A Made Sri Arjani; Dewa Ayu Agustini Posmaningsih; I Wayan Jana; Nur Habibah (Health Notions, 2018)
Various ways have been applied to free Bali from the spread of rabies virus. Socialization / counseling to increase knowledge and understanding of the community about rabies and its prevention has been implemented. Rabies vaccination in rabies-transmitted animals has been done, even periodically every year mass rabies vaccinations have been held, and 2015 is the sixth vaccination of rabies. Reduced wild dog populations or elimination have been performed. But rabies never stops, even today all districts in Bali are red zone rabies cases. This study aimed to measure the knowledge level of Pakraman Village leaders and community participation in identifying the potential of Pakraman Village and to analyze the model of community participation in rabies prevention. The subjects were 76 head of family in Tabanan District, Klungkung District, Bangli District, Karangasem District and Buleleng District. This study used pretest and posttest group design, ie a design to determine the impact of the treatment provided by measuring the level of community participation before and after intervention. Data on knowledge was collected by filling out questionnaires by 50 prajuru (administrators) of Pakraman Village before and after being given intervention in the form of counseling with art media of Bondres. Community participation data was collected through interviews before and after intervention. Potential data of Desa Pakraman and the pattern of community participation were collected through in-depth interviews and focus group discussions. Data analysis was done descriptively in the form of central tendency because of numerical data type. Hypothesis testing was done using Wilcoxon signed rank test. Based on the result of the research, it can be concluded that: 1) effective health education to increase knowledge of village administrator and public participation in eradicating rabies virus; 2) pattern / model of community participation in eradication of rabies virus more dominant influenced by visit / suggestion. Furthermore, it is suggested that village administrator pakraman to be more intent to make visits / suggestions to educate the society so that community participation is more increased. In addition it also needs mentoring from the government in educating the community so that more effective coaching. Keywords: Rabies, Pakraman village, Knowledge, Participation